Case report: Virus-induced hemophagocytic lymphohistiocytosis in a patient with APECED - Boyarchuk, Oksana; Dyvonyak, Olha; Hariyan, Tetyana; Volokha, Alla (Frontiers in Pediatrics, 2023)
Autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED), also known as autoimmune polyglandular syndrome type 1 (APS-1) is a rare autosomal recessive inborn error of immunity (IEI), which is accompanied by immune dysregulation. Hypoparathyroidism, adrenocortical failure and candidiasis are its typical manifestations. Here we report about recurrent COVID-19 in a 3-year-old boy with APECED, who developed retinopathy with macular atrophy and autoimmune hepatitis after the first episode of SARS-CoV-2 infection. Primary Epstein-Barr virus infection and a new episode of SARS-CoV-2 infection with COVID pneumonia triggered the development of severe hyperinflammation with signs of hemophagocytic lymphohistiocytosis (HLH): progressive cytopenia (thrombocytopenia, anemia, lymphopenia), hypoproteinemia, hypoalbuminemia, high levels of liver enzymes, hyperferritinemia, increased triglycerides levels; and coagulopathy with a low level of fibrinogen. Treatment with corticosteroids and intravenous immunoglobulins did not lead to a significant improvement. The progression of HLH and COVID-pneumonia resulted in a fatal outcome. The rarity and varied presentation of the HLH symptoms led to diagnostic difficulties and diagnosis delay. HLH should be suspected in a patient with immune dysregulation and impaired viral response. Treatment of infection-HLH is a major challenge due to the difficulties in balancing immunosuppression and management of underlying/triggering infection.